Applied Improvisation Enhances the Effects of Behavioral Activation on Symptoms of Depression and PTSD in High School Students Affected by the Great East Japan Earthquake - Sugiyama, Chikaze; Koseki, Shunsuke; Niikawa, Yoko; Ito, Daisuke; Takahashi, Fumito; Ishikawa, Rie (Frontiers in Psychology, 2021)
Background The education system can serve as a community-based resource to support the provision of long-term follow-up care after large-scale disasters. While school-based interventions conducted after a disaster have been confirmed to reduce symptoms of depression and posttraumatic stress disorder (PTSD), adolescents often exhibit low treatment motivation. Traditional methods used to encourage treatment motivation include fun activities, such as applied improv (AIM). This study evaluated the intervention effects and improved motivation of an intervention program combining AIM with the behavioral activation approach (BAA). Methods Participants were 253 tenth graders, who were in fifth grade at the time the Great East Japan Earthquake of 2011, and 239 students were included in the analyses. Participants were divided into two groups: the BAA and AIM + BAA groups. Students in each group participated in one class-wide intervention session, which lasted 60 min. Depression, PTSD symptoms, behavioral activation, avoidance, and resilience were evaluated using psychological scales. A participant’s evaluations of the intervention were confirmed using the impression sheet consisting of six items that measure comprehension, difficulty, efficacy, generalization, confirmation of a specific situation, and motivation. Results A two-way analysis of variance (ANOVA) conducted using data from the psychological scale did not reveal a significant effect from the intervention program. However, the Mann-Whitney U-test, which used data from the impression sheet, showed a significant effect on comprehension (p = 0.001), generalization (p = 0.023), and motivation (p = 0.025). Conclusion This study did not confirm the effectiveness of the BAA in reducing symptoms of depression and PTSD in adolescents. Regarding treatment motivation, the AIM + BAA group reported higher motivation than the BAA group. Thus, one session of AIM may contribute to improved treatment motivation in adolescents. AIM creates a safe environment and encourages engagement and participation in interventions. Treatment motivation is an important issue in adolescent therapy, and AIM may help solve this problem.